Visualising the Critical: Artistic Convention and Eclecticism in Oscar Wilde's Writings on the Decorative Arts - van der Plaat, Deborah (Australasian Journal of Victorian Studies, 2015)
In the mid-nineteenth century, the German naturalist Alexander von Humboldt (1769–1859) published his scientific study, Cosmos: A Sketch of the Physical Description of the Universe (1849). In this text Humboldt inverted the Romantic doctrine that associated imagination or artistic agency with a superior faculty and artistic genius with the gifted few. Arguing that the imagination was present within all people, but that it often lay dormant, especially among the masses, Humboldt also suggested it could be activated by contrasting botanical species from tropical and temperate climates. Such juxtapositions, he believed, could induce “more vivid impressions in the minds of [the] less highly gifted . . . heightening their powers of artistic creation” (Humboldt 454). This idea built upon his hypothesis that the greater a region’s biodiversity, the better an individual may grasp the inherent unity binding nature’s infinite variety. Seeking the similarities binding “strongly contrasting forms” the “spontaneous impressions of the untutored mind” would lead, “like the laborious deductions of the cultivated intellect, to the same intimate persuasion, that one sole and indissoluble chain binds together all nature” (5–6).